Can We Select Sugarbeet Harvesting Dates Using Drone‐based Vegetation Indices?. (1st June 2019) - Olson, Dan; Chatterjee, Amitava; Franzen, David W.
Abstract : In the Northern Great Plains, sugarbeet ( Beta vulgaris L.) harvesting is stretched out from August to October. Sensors mounted on unmanned aerial vehicles (UAVs) may provide the information needed to identify sugarbeet approaching an optimum harvesting date that maximizes the recoverable sugar yield. The objective of this study was to relate the vegetation indices at early‐ and late‐harvest time with corresponding sugarbeet root yield, sugar concentration, and recoverable sugar yield (RSY) at three fields in the Red River Valley of North Dakota and Minnesota during 2017 and 2018. Vegetation indices was determined based on the multispectral imagery collected using UAV. Early harvest dates (19 Sept. 2017 and 21 Aug. 2018) reduced yield and RSY in 5 of 6 site‐years, compared to late harvest dates (3 Oct. 2017, 4 Sept. 2018, and 18 Sept. 2018). In general, delaying harvest increased red normalized difference vegetation index (NDVI) and reduced red edge NDVI (RENDVI). However, Pearson correlation between yield and vegetation indices did not show consistent relationship across harvesting date, site, and growing season. Pooling all site‐year data showed a significant relationship between RENDVI and yield and RSY. Use of in‐season yield estimate (RENDVI/growing degree days) has potential to explain 46% of sugarbeet root yield and RSY. Core Ideas Sugarbeet yield and sugar content is directly related to the length of growing season. Late harvest in September increased recoverable sugar yield. Sugar concentration did not change with harvest date. Association between drone‐based indices and yield varied with site‐year.